How Does Dockless Bike-Sharing System Behave by Incentivizing Users to Participate in Rebalancing? - Yanjie Ji; Xue Jin; Xinwei Ma; Shuichao Zhang (IEEE Access, 2020)
Dockless bike-sharing has provided a flexible and convenient travel mode in recent years, with which shared bikes can be rented and returned easily. However, addressing the imbalance between demand and supply effectively becomes a major challenge to guarantee the sustainability of such systems. Vehicle-based approach results in substantial operating costs and more emissions. This study proposed a user-based model to incentivize users to participate in bike rebalancing. This model contains three important components: 1) determination of a bike surplus region by sorting surplus level in descend order; 2) determination of a bike deficient region from the perspective of users' utility maximization; and 3) updating the states of regions. Several numerical tests were implemented to evaluate the model's performance based on predefined parameters and historical trip data in downtown of Nanjing. As the results indicate, unmet demand can be greatly reduced if providing a certain level of monetary incentive. Different values of the maximum acceptable walking distance make little difference in demand loss and operating cost at a low level of incentive. With regard to the users, it implies that higher proportion of cooperative customers who are willing to participate in rebalancing can lead to a larger reduction of unmet demand. In addition, using surplus level as the index to define bike surplus regions is beneficial to saving the overall operating cost.